Regional Government's Role in Inclusive Deliberative Democracy for the Regent Election in Tolitoli Amid the Covid-19 Pandemic - Bahri, Syamsul; Amijaya, Meldi (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The implementation of the election of the regent and deputy regent of Tolitoli Regency in the midst of a pandemic presents challenges that threaten security stability, disrupted information connectivity due to the pandemic invites risks that endanger the implementation of the election of the regent and deputy regent, as the main key to ensuring the democratic process runs according to plan, avoiding security disturbances, the regional government is considered important in carrying out its role in ensuring the deliberation process for inclusive participation in the election of the regent and deputy regent in the context of general government affairs, especially in fostering national insight and national resilience in order to strengthen the practice of Pancasila, the implementation of the 1945 Constitution of the Republic of Indonesia, the preservation of Bhinneka Tunggal Ika and the defense and maintenance of the integrity of the Unitary State of the Republic of Indonesia. This study aims to investigate the extent of the role and support of the district government in building deliberation for Inclusive participation in the implementation of the democratic process in Tolitoli Regency which took place amidst the pandemic, a deep understanding was obtained by tracing its commitment to the ideal aspects reflected in the fulfillment of the formal conditions of deliberative democracy which are reflected in the absence of an exclusive place for certain parties in a discussion participation on relevant themes, or the absence of restrictions in the form of prohibitions on discussing relevant information, this study shows a positive trend in government commitment, inclusive participation is answered as shown in the condition where all segments in society are part of every policy presented in the implementation of the regent election amidst the threat of a pandemic, which is the priority of deliberative democracy.